2023
DOI: 10.3390/ijms24044180
|View full text |Cite
|
Sign up to set email alerts
|

Stable Expression of dmiR-283 in the Brain Promises Positive Effects in Endurance Exercise on Sleep–Wake Behavior in Aging Drosophila

Abstract: Sleep–wake stability is imbalanced with natural aging, and microRNAs (miRNAs) play important roles in cell proliferation, apoptosis, and aging; however, the biological functions of miRNAs in regulating aging-related sleep–wake behavior remain unexplored. This study varied the expression pattern of dmiR-283 in Drosophila and the result showed that the aging decline in sleep–wake behavior was caused by the accumulation of brain dmiR-283 expression, whereas the core clock genes cwo and Notch signaling pathway mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…A recent study has identified another potential mechanistic target of exercise in this context, a micro-RNA, dmir283, that may also be involved in the beneficial effect of exercise on aging circadian rhythms [58]. While our study focuses on a circadian mutant rather than age-related decline of circadian rhythms, this micro-RNA may be another avenue to investigate the mechanisms behind the rescues demonstrated here.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study has identified another potential mechanistic target of exercise in this context, a micro-RNA, dmir283, that may also be involved in the beneficial effect of exercise on aging circadian rhythms [58]. While our study focuses on a circadian mutant rather than age-related decline of circadian rhythms, this micro-RNA may be another avenue to investigate the mechanisms behind the rescues demonstrated here.…”
Section: Discussionmentioning
confidence: 94%